Psychometric properties of the Dental Fear Schedule Subscale in a Portuguese pediatric population: exploratory study - Inês Esteves; Andreia Costa; Ana Coelho Canta; Sónia Mendes (Revista Portuguesa de Estomatologia, Medicina Dentária e Cirurgia Maxilofacial)
Objectives: To conduct a psychometric evaluation of the Dental Fear Schedule Subscale-Short Form (DFSS-SF) in a Portuguese pediatric population. Methods: In this cross-sectional study, the DFSS-SF was applied to a convenience sample of 48 children (aged 3–9 years) in a university dental clinic. Child behavior during the consultation was assessed using the Frankl Behaviour Rating Scale (FBRS). The analysis included item frequency, internal consistency (Cronbach's α), and factor structure of the DFSS-SF. Criterion validity was assessed by correlating the DFSS-SF and FBRS scores (Spearman correlation). Discriminant validity was analyzed using the variables sex, age, treatment complexity, and child´s behavior during the appointment, employing the Mann-Whitney test (for items) and Student’s t test (for the scale's total score) (α=0.05). Results: Anxiety prevalence was 20.8%. Items linked to higher anxiety included extractions, injections, and drills. Items showed good distribution, and the scale's internal consistency was α=0.49. Factor analysis identified two factors: “Fear of unknown people” and “Fear of invasive procedures,” explaining 54.1% of the variance. A significant inverse correlation was observed between DFSS-SF and FBRS scores (r=-0.346; p=0.008). Younger children exhibited higher anxiety levels (p=0.03). Conclusion: The DFSS-SF demonstrated adequate performance in assessing anxiety related to dental consultations in the studied sample. Items showed good distribution and inter- item correlation. Internal consistency was acceptable, and there was an inverse correlation between anxiety and the child's behavior.